Дослідження плавності руху машинно-тракторного агрегату з перемінною масою при виконанні транспортної роботи - Кожушко, Андрій Павлович (Харківський національний автомобільно-дорожній університет, 2019)
Наведено результати моделювання пов’язаних коливань машинно-тракторного агрегату з напівпричіп цистерною та з причіп-цистерною в ході прямолінійного руху при виконанні транспортної роботи. Встановлено вплив значення радіальної жорсткості шин колісного трактора на горизонтальні, вертикальні прискорення та переміщення сидіння тракториста при виконанні транспортної роботи з цистерною.

The disclosure of issues related to solving problems of transport work has always been relevant. Today, in the study of types of transport works used in agriculture, there is a problem in the study of the movement of machine-tractor unit with trailed or semi-trailer tanks, which are filled with liquid. Since the transportation of liquid cargo causes significant internal oscillations, the impact on the operation of the wheeled tractor and tank is significant. This process causes longitudinal and transverse instability, which contributes to the increase of both energy costs and emergency situations (there is an effect on vibrations of motion, controllability and stability of the vehicle, increasing the dynamic loading of the running system, etc.). The goal of the work is to study the smoothness of the machine-transport unit with variable weight (semitrailer-tank and tank-trailer) by simulating the vibrational system of the vehicle. Namely, to study the effect of forced oscillations on the movement of a semi-trailer tank and a trailer tank, as well as when varying the rigidity of the tires of the wheeled tractor. In solving the set goal, a methodology was used which included the analysis of the results of mathematical modeling of the vibration of the wheeled tractor and the tank with a liquid containing a free surface in the dynamic solution of the problem. The model used takes into account the redistribution of liquid in the tank, which is caused by fluctuations of the shell, using the characteristics of the Rayleigh surface waves. As a result, the data of theoretical research, which take into account the variable weight of the semi-trailer and trailer unit during the performance of the machine-tractor unit of transport work with varying rigidity of tires, is obtained. The originality is in determining the dependence of the rigidity index of the wheels of the wheeled tractor on the smoothness of the machine-tractor unit with a semi-trailer and trailer tanker. The practical value of the work is in the recommendations on the use of one or another pressure in the tires of the wheeled tractor during operation.
Investigating ride quality of the machine-tractor unit with a variable mass during transport work
Keywords: трактор колісний; цистерна; коливання; перерозподіл мас; wheeled tractor; tank; vibrations; mass redistribution